SIMULASI MODEL MATEMATIKA GERAK PENDULUM SEDERHANA - Arwin Tsalas (MATHunesa: Jurnal Ilmiah Matematika, 2019)
Periodic motion of pendulum indicates that a simple pendulum moves harmonically to the oscillation angle. Following this in fulfilling the exact period form of a simple pendulum an image is made showing angular displacement plotted as a function in time different from the initial amplitude. To do it all requires a computer program to make it real. The computer program used by the author is Maple 18. then is used the damping-free differential equation model of a simple pendulum. Where there is angular displacement and time. Next there is the angular frequency used to compose a simple pendulum motion equation. Next, it uses Jacobi elliptic function which contains complete and incomplete elliptic integral functions. There are four times the oscillation period which is measured by the number of pendulums swinging so that the simple pendulum motion is obtained from using the jacobi elliptic function with an oscillation amplitude value between 75 and 90. Keywords : Simple Pendulum, Jacobi of Elliptical Function, Elliptical Integral.